¿Contradicciones entre instrumentos de gestión territorial? Notas en torno a dos piezas de normativa urbanística en Santo Tomé (Santa Fe) (Papeles, 2021)
The article analyzes two policies currently in force in the city of Santo Tomé (Santa Fe) that regulate the use of urban land: one that, through urban agreements, proposes the recovery, by the local State, of the appraisal of the land generated by its decisions regarding urban regulation to, based on it, provide collective equipment and/or infrastructure that contributes to greater equity in urban development and less speculation and land retention. The second policy allows social organizations of the city to use vacant land lots (which are valued during that time) on loan for three years, exempting their owners from paying the corresponding fees, thus not stimulating a greater supply of land in the market nor the completion and densification of the urban plant. Taking these documents as a source of information, the research points out the disarticulation, inconsistency and/or normative contradiction in which the Santotomian State incurs, which, in part at least, does not contribute to correct an unbalanced urban growth.
Keywords: Capital gains recovery; Urban regulations; Territory management; Santo Tomé